Nanoscale pore structure in anthracite coals and its effect on methane adsorption capacity - Xu, Qiang; Wang, Ruyue; Wang, Zebin; Zhao, Yue; Miao, Quanyun; Zhang, Zhengguang; Bai, Xiujia; Xinxin, Feng (Frontiers in Earth Science, 2024)
Although significant amounts of methane are present in anthracite coal seams, coalbed methane resources cannot be extracted effectively and quickly. This study mainly focused on investigating the pore system and methane adsorption capacity to clarify the storage of coalbed methane. Anthracite coal samples from the Anzenan coalbed methane block in China were collected, and pore characterization methods (low-pressure N2 adsorption, mercury injection experiments, and scanning electron microscopy (SEM) observations) and methane isothermal adsorption experiments were conducted. The results showed that few mesopores and nanoscale macropores were present in the anthracite coal samples. The volume of the 2–300 nm pores in these coal samples obtained from the N2 adsorption experiment was lower than 0.01 cm3/g. SEM observations also revealed that only a small number of mesopores and nanoscale macropores could be seen, and most of these pores were isolated. In terms of the methane isothermal adsorption data, it was found these anthracite coals have a large methane adsorption capacity, and the Langmuir volume ranges from 19.5 to 28.4 cm3/g, with an average of 22.2 cm3/g. With increasing ash yield, the Langmuir volume decreased linearly, indicating that methane molecules were mainly adsorbed in the organic matter of coal. As methane is mainly adsorbed in the micropores of coal organic matter and there are few mesopores and nanoscale macropores in the organic pores in coal, there are not enough tunnels to transport the adsorbed methane molecules to the outside. Thus, it is difficult to extract coalbed methane from anthracite. This study reveals the impact of pore system limitations on the storage and extraction of coalbed methane in anthracite coal. The findings can be applied to the extraction of coalbed methane from anthracite coal seams worldwide.